PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN DIGITAL MARKETING DALAM MENINGKATKAN PROMOSI KARYA SILVER DI CELUK SUKAWATI - Ayu Made Bianca Juarez; Dewa Putu Arix Setia Sumantri (Bajang Institute, 2025)
This study explores the impact of a digital marketing skills training program organized by the Faculty of Social Sciences and Humanities, Universitas Pendidikan Nasional (UNDIKNAS) in Celuk Sukawati, Bali, specifically for silversmiths. In the rapidly evolving digital era, silversmiths face competitive challenges in marketing their products and maintaining the quality and uniqueness of their crafts. Using a qualitative approach, data was collected through interviews, direct observations, and focus group discussions to understand the craftsmen's needs and challenges. The training program aimed to improve the craftsmen's digital skills, introduce various marketing techniques, and prioritize design innovation and product quality. The results of this program show significant improvements in artisan skills, reflected in improved product quality and sales. Marketing through social media and e-commerce has successfully expanded market reach and realized local economic potential. The program has also had a positive impact on job creation and the preservation of silver craft culture, as artisans are expected to maintain traditions while innovating. The evaluation recommends conducting more specific advanced training, establishing collaborations with government and private institutions, and strengthening the infrastructure necessary for implementing digital marketing strategies. With active community involvement, this program is expected to not only improve the sustainability of the silver craft industry in Celuk but also create an empowerment model that can be adapted to other communities. The results of this study indicate that planned training and appropriate support have a significant impact on the success of the local economy and the preservation of silver craft culture in Indonesia